Dietary Intervention Reverses Fatty Liver and Altered Gut Microbiota during Early-Life Undernutrition - K. C. Bauer (American Society for Microbiology, 2020)
ABSTRACT Nonalcoholic fatty liver disease (NAFLD), largely studied as a condition of overnutrition, also presents in undernourished populations. Like NAFLD, undernutrition disrupts systemic metabolism and has been linked to gut microbiota dysbiosis. Indeed, chronic exposures to fecal microbes contribute to undernutrition pathology in regions with poor sanitation. Despite a growing prevalence of fatty liver disease, the influence of undernutrition and the gut microbiota remain largely unexplored. Here, we utilize an established murine model (C57BL/6J mice placed on a malnourished diet that received iterative Escherichia coli/Bacteroidales gavage [MBG mice]) that combines a protein/fat-deficient diet and iterative exposure to specific, fecal microbes. Fecal-oral contamination exacerbates triglyceride accumulation in undernourished mice. MBG livers exhibit diffuse lipidosis accompanied by striking shifts in fatty acid, glycerophospholipid, and retinol metabolism. Multiomic analyses revealed metabolomic pathways linked to the undernourished gut microbiome and hepatic steatosis, including phenylacetate metabolism. Intriguingly, fatty liver features were observed only in the early-life, but not adult, MBG model despite similar liver metabolomic profiles. Importantly, we demonstrate that dietary intervention largely mitigates aberrant metabolomic and microbiome features in MBG mice. These findings indicate a crucial window in early-life development that, when disrupted by nutritional deficiency, may significantly influence liver function. Our work provides a multifaceted study of how diet and gut microbes inform fatty liver progression and reversal during undernutrition. IMPORTANCE Nonalcoholic fatty liver disease (NAFLD) remains a global epidemic, but it is often studied in the context of obesity and aging. Nutritional deficits, however, also trigger hepatic steatosis, influencing health trajectories in undernourished pediatric populations. Here, we report that exposure to specific gut microbes impacts fatty liver pathology in mice fed a protein/fat-deficient diet. We utilize a multiomics approach to (i) characterize NAFLD in the context of early undernutrition and (ii) examine the impact of diet and gut microbes in the pathology and reversal of hepatic steatosis. We provide compelling evidence that an early-life, critical development window facilitates undernutrition-induced fatty liver pathology. Moreover, we demonstrate that sustained dietary intervention largely reverses fatty liver features and microbiome shifts observed during early-life malnutrition.